Control of master-slave microgrid based on CAN bus - Alfergani, Asma; Khalil, Ashraf; Rajab, Zakariya; Zuheir, Mohammad; Asheibi, Ali; Khan, Sheroz; Aboadla, Ezzidin Hassan Elmabrouk; Azna, Khairil Azhar; Tohtayong, Majdee (Institute of Electrical and Electronics Engineers Inc., 2018)
In this paper, the control of parallel voltage-source inverters Microgrid based on Controller Area Network (CAN) is introduced. The design is based on the maximum time delay that guarantees the stability where the system is composed of threephase DC/AC inverters with master-slave control strategy in the rotational reference frame (dq frame). The reference current signals are sent from the master to the slave converters through Controller Area Network bus (CAN bus). A model for masterslave communication-based Microgrid is presented and the system is modeled as a general time delay system. The maximum time delay that guarantees the stability of the system is calculated using a Lyapunov-Krasovskii based linear matrix inequalities method. The results are tested through Matlab/Simulink and True-Time 2.0 simulation.